Artificial intelligence in performance-driven design : theories, methods, and tools - Abbasabadi, Narjes; Ashayeri, Mehdi; Ohio Library and Information Network (Hoboken, New Jersey : Wiley, 2024)
"The recent advances in data-driven approaches and big data initiatives provide enormous opportunities for sustainable design and research in decarbonization and digital transformation of the built environment. The Artificial Intelligence and Sustainable Design: Theories, Methods, and Tools book aims to comprehensively review the application of Artificial Intelligence (AI), particularly Machine Learning (ML), in enhancing performance-based design and offer advanced insight into different approaches, methods, and tools for bringing the power of AI in simulation platforms and leveraging digital twin throughout the life cycle of the built environment. The contents center on fundamentals of building science, including key performance indicators such as comfort, indoor/outdoor environmental quality, solar and daylight, and energy exploring human-centered and evidence-based design and optimization procedures and integrating intelligent systems for better understanding, designing, and managing our existing and future built environments"--
Includes bibliographical references and index
Keywords: Artificial intelligence -- Industrial applications; Engineering design -- Data processing